Innovation in Information Technology-Based School Management in Renewed Education 5.0 - Maharani, Adelia (JME Jurnal Management Education, 2025)
This article discusses innovations in school management based on information technology to support Education 5.0, which integrates digital technology with humanistic values to create an adaptive, inclusive, and responsive education system in line with modern developments. Education 5.0 emphasizes character building, creativity, and critical thinking skills in students, as well as the development of multidimensional competencies to face future challenges. However, the implementation of Education 5.0 faces challenges such as limited infrastructure, educators' digital skills, and inflexible educational policies. In the context of school management, technologies like digital management systems, AI, Big Data, IoT, and blockchain can improve efficiency, transparency, and security, while supporting personalized learning. The use of these technologies not only enhances administrative management but also creates a more adaptive and inclusive learning experience, ultimately improving the overall quality of education.